2022
DOI: 10.14245/ns.2142942.471
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of 3 Types of Minimally Invasive Posterior Cervical Foraminotomy for Foraminal Stenosis, Uniportal-, Biportal Endoscopy, and Microsurgery: Radiologic and Midterm Clinical Outcomes

Abstract: Objective:The aim of this study was to compare the clinical and radiologic outcomes of three types of minimally invasive posterior cervical foraminotomy (PCF): uniportal endoscopic surgery, biportal endoscopic surgery, and microsurgery.Methods: Between January 2019 to January 2020, PCF was performed using three different approaches to treat foraminal stenosis. The foraminal expansion rate, facet resection rate, and surgical foraminal approach angle were measured using magnetic resonance imaging. Visual analog … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 18 publications
(32 reference statements)
0
24
0
Order By: Relevance
“…[7][8][9][10] Endoscopic systems offer a multiaxial viewing angle and a magnified clear endoscopic view that enable detailed bone decompression using various approaches. 9,11 A recent comparative study by Kim et al 12 revealed that endoscopic PCF offered enhanced facet joint preservation and improved midterm clinical results compared to microscopic PCF. Furthermore, full endoscopy offers a safe surgical route for ventral foraminal decompression via partial pediculotomy or partial vertebrotomy, and it shows good surgical outcomes.…”
Section: Neurospine Eissn 2586-6591 Pissn 2586-6583mentioning
confidence: 99%
See 1 more Smart Citation
“…[7][8][9][10] Endoscopic systems offer a multiaxial viewing angle and a magnified clear endoscopic view that enable detailed bone decompression using various approaches. 9,11 A recent comparative study by Kim et al 12 revealed that endoscopic PCF offered enhanced facet joint preservation and improved midterm clinical results compared to microscopic PCF. Furthermore, full endoscopy offers a safe surgical route for ventral foraminal decompression via partial pediculotomy or partial vertebrotomy, and it shows good surgical outcomes.…”
Section: Neurospine Eissn 2586-6591 Pissn 2586-6583mentioning
confidence: 99%
“…We measured 4 parameters to document the changes in the neural foraminal space and facet on the pre-and postoperative T2-weighted MRI using the methods described by Nakamura and Taguchi 17 and Kim et al 12 Two values for the middle and distal foraminal widths and one for the facet length were measured on axial MRI from the intervertebral disc levels. One foraminal height value was measured on oblique sagittal MRI from the middle pedicle level.…”
Section: Radiologic Parametersmentioning
confidence: 99%
“…Minimally invasive tubular techniques have demonstrated clinical effectiveness on par with open PCF but with less blood loss, analgesic use, immediate postoperative neck pain, and hospital length of stay 19,20. Endoscopy allows surgeons to accomplish PCF in an even less traumatic fashion—resulting in less postoperative neck pain and shorter hospital stays than other techniques—without sacrificing clinical effectiveness 11,12…”
Section: Clinical Effectivenessmentioning
confidence: 99%
“…19,20 Endoscopy allows surgeons to accomplish PCF in an even less traumatic fashion-resulting in less postoperative neck pain and shorter hospital stays than other techniques-without sacrificing clinical effectiveness. 11,12 The benefits of endoscopic techniques extend beyond preservation of the paraspinal soft tissues. The angled optics of the endoscope allow for viewing deeper within the foramen, and the narrow endoscopic working cannula can be oriented in a more medial-to-lateral trajectory before abutting the spinous process than can a conventional tubular retractor-these features both permit more extensive SAP undercutting.…”
Section: Clinical Effectivenessmentioning
confidence: 99%
See 1 more Smart Citation